The factor structure of the Social Axioms Survey II (SASII) in the South African context. Issue 6 (11th December 2017) - Barnard, Adi; Meiring, Deon; Rothmann, Ian
Abstract : The objective of this study was to validate the new Social Axioms Survey II (SASII). The study sample comprised university students ( n = 793) as well as their family members and friends ( n = 645). Confirmatory factor analysis (CFA) following an initial exploratory factor analysis yielded a five-factor model: social cynicism, social complexity, reward for application, religiosity, and fate control. The findings of this study support the use of the new SASII in South Africa for research purposes.